Perancangan Sistem Restorasi Citra Dengan Metode Image Inpainting - Abdul Halim Hasugian; Ilka Zufria (ALGORITMA : JURNAL ILMU KOMPUTER DAN INFORMATIKA, 2018)
Image Inpainting method is a technique of modifying images without being detected. The purpose of thisapplication is starting from the restoration of damaged paintings and photography to removing or replacingcertain objects. Image inpainting is one method of image restoration for confronting images that are slightlydamaged such as scratched or streaked where filling the area will be restored based on information around thearea so that the restoration is carried out completely in that area. Image restoration is often used in improvingimage quality where in this image restoration focuses on repairing damaged images, either during thedigitization process or due to intentional or accidental processes.Keywords: Image Restoration, Inpainting Method, design